Haptoglobin genotypic distribution in Iranian patients with coronary heart disease - Kazemi, Bahram; Khalkhal, Ensieh; Shabani, Ashraf (Archives of Advances in Biosciences, 2011)
<!–[if gte mso 9]> Normal 0 false false false EN-US X-NONE AR-SA MicrosoftInternetExplorer4 <![endif]–><!–[if gte mso 9]> <![endif]–><!–[if gte mso 10]> <![endif]–> Haptoglobin is a plasma protein with hemoglobin binding capacity. Haptoglobin has important biological functions such as binding to free hemoglobin and removes it from the circulation, thus preventing iron loss and kidney damage during intravascular hemolysis, superior antioxidant capacity, protection against free radicals. Studies on the distribution of Hp show that the gene frequencies of Hp dependent on geographical and genetic family. In the other, several authors have showed the correlation between HP types and different diseases, such as inflammation, infection, cardiovascular diseases and malignant tumors.Smoking, hypertention,diabetes mellitus and serum lipid concentrations are risk factors for developing cardiovascular diseases. In addition, Hp polymorphism has been proposed as a risk factor for developing atherosclerotic vasculare disease. In this study, the association between Haptoglobin genotypic distribution and the incidence of coronary heart disease investigated. 50 Iranian patients with coronary heart disease were randomly selected. Genomic DNA extracted from peripheral blood leukocytes. In PCRs with primers A and B, amplification products of 1757 and 3481 bp were amplified from genomic DNA containing alleles Hp1 and Hp2, respectively. In the population studied, the distribution of haptoglobin polymorphism was 36% (n = 18) for the Hp1-1 type, 62% (n =31) for the HP1-2 type, and 2% (n = 1) for the HP2-2 type. The trend in this study showing a lower frequency of 3-vessel disease and less severe coronary artery stenosis in patients with the HP1-1 phenotype than in patients with the HP1-2 phenotypes may be indicative of a protective effect of the HP1-1 phenotype against the development of atherosclerotic coronary artery disease.